2018
DOI: 10.2355/isijinternational.isijint-2018-202
|View full text |Cite
|
Sign up to set email alerts
|

Local Buckling of Steel Plates in Composite Structures under Combined Bending and Compression

Abstract: In this paper, explicit local buckling analysis of steel plates in composite structures under combine bending and compression and with elastic restraint against rotation is presented. Unique displacement function, which combines sinusoidal and cosine functions along x-and y-directions and satisfies boundary and loading conditions, is proposed to account for the effect of restraint of concrete and the elastic rotational restraint stiffness along both the loaded and unloaded edges of the steel plates. The explic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Although nucleation deformation depends on the stress state, it has been found that the phase boundary strength is only very weakly affected by the stress state and the level of plastic deformation [4]. Due to the non-homogeneity of plastic deformation, it is difficult to estimate the maximum stress value at the phase boundary [6]. The original model of phase boundary strength [7] was later elaborated by Brown and Stobbs [8], who estimated phase boundary strength as the sum of local stress E and the yield strength 0m of the basic matrix, where…”
Section: Model Of Cavity Nucleation In Ductile Fracturementioning
confidence: 99%
“…Although nucleation deformation depends on the stress state, it has been found that the phase boundary strength is only very weakly affected by the stress state and the level of plastic deformation [4]. Due to the non-homogeneity of plastic deformation, it is difficult to estimate the maximum stress value at the phase boundary [6]. The original model of phase boundary strength [7] was later elaborated by Brown and Stobbs [8], who estimated phase boundary strength as the sum of local stress E and the yield strength 0m of the basic matrix, where…”
Section: Model Of Cavity Nucleation In Ductile Fracturementioning
confidence: 99%
“…Emero [5] presented an optimization algorithm with respect to the reinforcement arrangements, the sizes, intervals and lengths of stiffened ribs were optimized for better buckling resistance of the rectangular plates. Besides, Qin [6] researched the local buckling of composite plates under bending, compression and elastic restraints. In general, the current methods on anti-buckling design of rectangular tubes mainly focus on structural modification or material reconstruction.…”
Section: Introductionmentioning
confidence: 99%